Antibiotic Resistance Pattern of Bacterial Isolates from Post- Tracheostomised Patients Attending Tertiary Care Hospital in Nepal - Thapa, Eliza; Thapa, Roshan; Singh, Anjana; Pokharel, Bharat Mani; Devkota, Upendra (Journal of Institute of Science and Technology, 2016)
The bacterial profile and their drug susceptibility pattern was studied in post-tracheostomised patients admitted in National Institute of Neurological and Allied Sciences. Identification of organisms was done by standard microbiological techniques and antibiogram was performed by Kirby Bauer disc diffusion method according to Clinical and Laboratory standard (CLSI) guidelines. Significant growth was observed in 58.6% samples with polymicrobial growth in 19.5% samples among the total positive cultures. Pseudomonas aeruginosa was the predominant organism (34.2%) followed by Acinetobacter spp. (31.8%), Escherichia coli (8.9%), Klebsiella pneumoniae (6.0%), Citrobacter fruendii (5.6%), Klebsiella oxytoca (4.0%), Providencia spp. and Staphylococcus aureus (2.8% each), Proteus mirabilis (2.4%) and Proteus vulgaris (1.2%) . More than 90% of Gram negative bacterial isolates were found resistant to Ampicillin, Cefixime, Cephotaxime. The most effective drugs against S. aureus were Vancomycin, Rifampicin, Amoxycillin and Clavulanic acid showing 100% sensitivity. Highest resistance rate was observed for Ampicillin (85.71%) and low for Gentamicin (14.28%). Findings of this study show emerging threat of multidrug resistant bacteria. Thus, periodic monitoring and assessing drug susceptibility pattern of bacteria and rational use of antibiotics in post tracheostomised patients were recommended. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 129-132